2016
DOI: 10.1007/s40572-016-0089-9
|View full text |Cite
|
Sign up to set email alerts
|

Recent Research Examining Links Among Klebsiella pneumoniae from Food, Food Animals, and Human Extraintestinal Infections

Abstract: Klebsiella pneumoniae is a colonizer of livestock, a contaminant of retail meats and vegetables, and a cause of extraintestinal infections in humans. Antibiotic-resistant strains of K. pneumoniae are becoming increasingly prevalent among hospital and community-acquired infections. Antibiotics are used extensively in conventional food-animal production, where they select for antibiotic-resistant bacteria. Antibiotic-resistant K. pneumoniae has been isolated from livestock as well as from a variety of retail mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
93
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(97 citation statements)
references
References 85 publications
2
93
1
1
Order By: Relevance
“…Reports in the 1970s--80s highlighted the ubiquitous distribution of K. pneumoniae among diverse fresh and salt water environments, plants, and soil [41]. K. pneumoniae causes infections in cows, horses and other wild and domestic animals [9,[42][43][44][45][46][47][48][49]. However as an opportunistic pathogen, it is likely that K. pneumoniae is more often a component of the normal animal gut microbiota.…”
Section: Ecological Rangementioning
confidence: 99%
See 2 more Smart Citations
“…Reports in the 1970s--80s highlighted the ubiquitous distribution of K. pneumoniae among diverse fresh and salt water environments, plants, and soil [41]. K. pneumoniae causes infections in cows, horses and other wild and domestic animals [9,[42][43][44][45][46][47][48][49]. However as an opportunistic pathogen, it is likely that K. pneumoniae is more often a component of the normal animal gut microbiota.…”
Section: Ecological Rangementioning
confidence: 99%
“…In humans the rate of intestinal K. pneumoniae colonisation has been estimated at 6% [50,51], while in dairy cows the rate may be much higher (~44% among herds in New York, USA, [52]). K. pneumoniae has also been cultured from the faeces of other agricultural and domestic animals, from the cloacae of birds, and from fish, shellfish, insects and earthworms [43,49,[53][54][55][56][57]. It is a common contaminant of animal and plant--based foods, which likely plays a key role in introducing environmental strains into the human gut [49].…”
Section: Ecological Rangementioning
confidence: 99%
See 1 more Smart Citation
“…Enterobacteriaceae found in livestock and on retail meat include the opportunistic pathogens Escherichia coli and Klebsiella (Davis and Price, 2016;Davis et al, 2015;Nordstrom et al, 2013), which are the most common causes of urinary tract infections and among the most common causes of bloodstream infections in patients (Davis and Price, 2016;Diekema et al, 2003;Laupland and Church, 2014;Laupland et al, 2007;Russo and Johnson, 2003;Wisplinghoff et al, 2004). Staphylococcus aureus, the most common cause of skin infections and second most common cause of bloodstream infections in patients (Brook and Frazier, 1995;Carratala et al, 2003;Diekema et al, 2001;Sigurdsson and Gudmundsson, 1989;Wisplinghoff et al, 2003a;Wisplinghoff et al, 2003b;Wisplinghoff et al, 2004), is also found on the skin of livestock and on retail meat (Smith, 2015;Smith and Wardyn, 2015).…”
Section: The Current State Of Antibiotic Resistancementioning
confidence: 99%
“…In the ensuing decades, numerous studies have been published in peer-reviewed scientific literature providing additional evidence of the spread of antibiotic-resistant microbes from livestock animals into the food supply or to humans (CDC, 2013b;Davis and Price, 2016;Elliott, 2015;Marshall and Levy, 2011;O'Neill, 2015;Robinson et al, 2016;Sneeringer et al, 2015). Indeed a recent report commissioned by the British government concluded the following:…”
Section: Introductionmentioning
confidence: 99%